Hyperhomocysteinemia in men with a reproductive history of fetal neural tube defects: Three case reports and literature review. Issue 2 (January 2019) - Yu, Yang; Jia, Chunshu; Shi, Qingyang; Zhu, Yueying; Liu, Yanhong
Abstract: Rationale: Hereditary hyperhomocysteinemia results from a polymorphism in the methylenetetrahydrofolate reductase (MTHFR) gene that reduces folate metabolism. Mutations in the MTHFR gene are common in parents who have given birth to children with neural tube defects (NTDs). Most research has focused on the risk for fetal NTDs in women with hyperhomocysteinemia and MTHFR gene mutations. Studies investigating the association between hyperhomocysteinemia, MTHFR gene mutations, and the risk for fetal NTDs in men are scarce. Patient concerns: Here, we report on 3 men with hyperhomocysteinemia and the MTHFR C677T homozygous TT genotype that have reproductive histories of fetal NTDs. Diagnosis: these 3 men were diagnosed as hyperhomocysteinemia and MTHFR C677T homozygous TT genotype. Interventions: Three men received homocysteine-lowering therapy. Outcomes: The first man's wife became pregnant, and a healthy infant was spontaneously delivered at term, the other 2 men's wives are still not pregnant. Lessons: Findings from this case reports and published literature imply that hereditary hyperhomocysteinemia in men affects sperm quality and sperm DNA methylation and causes epigenetic modifications that can result in fetal NTDs. We recommend monitoring homocysteine and folate levels in men before conception and supplementing with folate as needed, especially in men with a reproductive history of fetuses with neural tube or other birth defects.